Training on Hybrid Metaheuristics and its Applications From Theory to Implementations - Mritha, Ramalingam (Faculty of Computing, 2021)
PEKAN, 21 September 2021 - A training on course, 'Hybrid Metaheuristics and its Applications: From Theory to Implementations' was conducted online on 20 and 21 September 2021. This training was organized by Centre for Software Development and Integrated Computing (Software Centre), UMP.